The Role of Emotional Factors in Shaping Scientific Literacy Among Adolescents: A Case Study - Saputra, Winata Tegar; Rahmat, Adi; Winarno*, Nanang; Ahmad, Nur Jahan (Jurnal IPA & Pembelajaran IPA, 2025)
Academic achievement is not only influenced by their learning process but also by emotional and societal factors. This study examines the students profiles regarding scientific literacy and emotional factors. Also, the correlation on both sides is studied in one population. This study used a quantitative survey research design for 132 students in 9 grade secondary school. The emotional factors were divided into interest, enjoyment, and engagement regarding science learning, while the scientific literacy used PISA 2015 test items. It found that the result of scientific literacy among students is in the low category, with the average in both of them being 28.34 out of 100, with explain phenomena scientifically as the highest competency achievement, followed by design and evaluate scientific enquiry in the second highest and lastly interpret data and evidence scientifically as the lowest achievement competency. There are interest, enjoyment, and engagement factors in emotional factors, and the general average among the three is 3.02 out of 5.00, which includes the neutral category. The highest emotional factors for science learning are interest, enjoyment, and engagement, as the smallest value. The correlational study of scientific literacy to emotional factors was also conducted and showed 0.835, which includes a very strong category. Therefore, this study implicated insight into the curriculum design and training program for teachers to find better ways to accommodate the emotional needs of students